PELATIHAN PENGGUNAAN APLIKASI MICROSOFT OFFICE 365 BAGI PARA SISWA SLTA - Taufiqurrochman Taufiqurrochman; Tuhfatul Habibah Hasibuan; Jelman Nasri; Jhon Larsen; Khusnul Khoiriyah; Heru Winarno; Nur Sucahyo; Melati Wijaya (SWADIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
The era of globalization demands that students have adequate technological skills to compete in both the academic world and the world of work. Universities and the world of work currently require students to be proficient in Microsoft Office as a minimum skill. This training is important given the need to adapt to digital transformation in education and professional demands. Microsoft Office 365 is an industry standard in the professional world. The purpose of this Community Service (PKM) is to create a younger generation that is more skilled in using Microsoft Office 365 applications. The activity was conducted as a training session on the use of Microsoft Office 365 applications for high school students around the ITB Swadharma campus, with a total of 23 students from 11 schools. The results of the activity were an increase in students' skills in using Microsoft Office 365, especially the Check Box feature, Logical Function, Median Function, HLookup, Max and Min, Mode, Table, VLookup, and Worksheet. Meanwhile, the Combo Box feature, Concatenate Function, Graph, Pivot Table, and Document Protection, which are not yet fully mastered by students, can be used as material for further training.Era globalisasi menuntut para siswa memiliki keterampilan teknologi yang mumpuni agar dapat bersaing baik didalam dunia akademis maupun dunia kerja. Perguruan tinggi dan dunia kerja saat ini mewajibkan para siswa mahir Microsoft Office sebagai kemampuan minimal. Pelatihan ini menjadi penting dengan adanya kebutuhan adaptasi terhadap transformasi digital di dunia pendidikan dan tuntutan profesional. Microsoft Office 365 merupakan standar industri di dunia profesional. Tujuan dari Pengabdian Kepada Masyarakat (PKM) ini adalah menciptakan generasi muda yang lebih terampil dalam menggunakan aplikasi Microsoft Office 365. Kegiatan dilakukan dalam bentuk Pelatihan penggunaan aplikasi Microsoft Office 365 bagi Para siswa SLTA yang berada di sekitar kampus ITB Swadharma sebanyak 23 orang siswa yang berasal dari 11 sekolah. Hasil kegiatan adanya peningkatan keterampilan siswa dalam penggunaan Microsoft Office 365 khususnya fitur Check Box, Fungsi Logika, Fungsi Median, HLookup, Max dan Min, Modus, Tabel, VLookup, Worksheet. Sedangkan untuk fitur Combo Box, Fungsi Concatenate, Grafik, Pivot Tabel, dan Proteksi Dokumen yang belum terlalu dikuasai oleh siswa dapat menjadi bahan untuk pelatihan selanjutnya.